GUÍA PARA EL FORTALECIMIENTO DE LA LITERACIDAD: DESDE LA PEDAGOGÍA DE GÉNEROS, LA MULTIMODALIDAD Y EL USO DE LAS IA - Ferrer Mendoza, Yicera; Serrano Castro, Harold; Castellanos Fernández, Víctor Andrés (Corporación Universitaria Americana, 2024)
This guide aims to provide tools for strengthening literacy in literacy and the use of Artificial Intelligence (AI), consistent with current needs, therefore, it offers guidelines for teacher mediation using multimodal. It is based on Genre-based pedagogy and Systemic Functional Linguistics (SFL), which in general terms is assumed as a pedagogical and holistic perspective that responds to the needs posed by the economic, social and environmental environment, with a predominance of collaborative learning and in which, in turn, it is essential to show that textual production is a process developed in different phases that are oriented to achieve a specific communicative purpose.